Elucidating the Parasitic Capabilities of Trichoderma against Meloidogyne javanica on Tomato. Issue 1 (2011) - Golzari, Hadi; Panjehkeh, Naser; Ahmadzadeh, Masuod; Salari, Mohammad; Sedaghati-khoravi, Ebrahim
No abstract available